Light-scattering sensor for real-time identification of Vibrio parahaemolyticus, Vibrio vulnificus and Vibrio cholerae colonies on solid agar plate - Karleigh Huff (2018)
The three most common pathogenic species of Vibrio, Vibrio cholerae, Vibrio parahaemolyticus and Vibrio vulnificus, are of major concerns due to increased incidence of water- and seafood-related outbreaks and illness worldwide. Current methods are lengthy and require biochemical and molecular confirmation. A novel label-free forward light-scattering sensor was developed to detect and identify colonies of these three pathogens in real time in the presence of other vibrios in food or water samples. Vibrio colonies grown on agar plates were illuminated by a 635nm laser beam and scatter-image signatures were acquired using a CCD (charge-coupled device) camera in an automated BARDOT (BActerial Rapid Detection using Optical light-scattering Technology) system. Although a limited number of Vibrio species was tested, each produced a unique light-scattering signature that is consistent from colony to colony. Subsequently a pattern recognition system analysing the collected light-scatter information provided classification in 1-2min with an accuracy of 99%. The light-scattering signatures were unaffected by subjecting the bacteria to physiological stressors: osmotic imbalance, acid, heat and recovery from a viable but non-culturable state. Furthermore, employing a standard sample enrichment in alkaline peptone water for 6h followed by plating on selective thiosulphate citrate bile salts sucrose agar at 30°C for ~12h, the light-scattering sensor successfully detected V.cholerae, V.parahaemolyticus and V.vulnificus present in oyster or water samples in 18h even in the presence of other vibrios or other bacteria, indicating the suitability of the sensor as a powerful screening tool for pathogens on agar plates. © 2012 Society for Applied Microbiology and Blackwell Publishing Ltd.